Co-morbid diabetes mellitus in cancer patients undergoing treatment: a case series and perspective - H. U. V., Aisiri; Rao, Maanas R.; Ramani, Vinod K.; Naik, Radheshyam (Frontiers in Oncology, 2025)
IntroductionDiabetes mellitus (DM) is frequently diagnosed among cancer patients on treatment, which suggests a concomitant underlying mechanism. DM is found among 8 to 18% of cancer patients. The initiation of cancer treatment is linked with the onset of diabetes. This study aims to assess the variation in blood glucose levels of cancer patients during the course of their treatment.MethodsA hospital record based cross-sectional study was conducted from November 2024 to January 2025, among 50 cancer patients on treatment at Sammprada cancer hospital, Bangalore, India. From the initial 50 cancer patients, a series of 11 cases with large variation in blood glucose levels were included in the study. These include new onset or old cases of diabetes, with blood glucose levels measured across 6 timeframes during the course of cancer treatment.ResultsFor the initial 50 patients, the measure of central tendency seemed regressed to the mean. Hence, the design of study was changed from cross-sectional to a case series. For the series of 11 patients all of whom had advanced stage cancer, 5 patients (2 males, 3 females) had history of diabetes and 2 female patients were incident cases of diabetes (1 each in endocrine and cervical cancer). Also, the treatment for diabetes was revised or newly initiated for a total of 5 patients (4 females, 1 male).ConclusionAmong the 11 cancer patients, 5 had history of DM and 2 were incident cases of DM. Healthcare providers should regularly screen the levels of blood glucose during the continuum of cancer care and monitor the change in trend.